Determinants of Behavioral Compliance in Coronary Heart Disease Therapy Among Patients at Bandung Heart Clinic - Shabrina Arifia Qatrannada; Widjanarko, Bagoes; Handayani, Novia (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Coronary heart disease (CHD) ranks seventh among non-communicable diseases (NCDs) in Indonesia, with a projected increase in mortality by 2030 to approximately 23,6 million. The rehabilitation of CHD, which constitutes long-term treatment, significantly depends on patient adherence. Objective: This study aims to investigate the determinants of patient adherence behavior at the Bandung Heart Clinic. Methods: It employed a crosssectional research design, gathering data from 471 CHD patients with a history of atherosclerosis at the clinic between January and October 2022. The minimum sample size of 80 respondents, calculated using the Lemeshow formula, was increased to 150 to mitigate potential dropouts. The research instrument used was a questionnaire that had been validated and deemed reliable, except for one question regarding family support. Sampling was conducted using accidental sampling and involved interview data collection. Results: Bivariate data analysis, using the chi-square test, indicated significant associations between gender (p=0.09), employment status (p=0.01), health insurance participation (p=0.012), healthcare accessibility (p=0.022), family support (p=0.006), and treatment motivation (p=0.22) with patient adherence behavior. Additionally, female patients (OR=3,316) patients who are members of a health insurance (OR=2,617), patients with high treatment motivation (OR=1,983), patients who receive support from their families (OR=2,476) are more likely to exhibit adherence behavior compared to those who are not. Conclusion: In summary, it can be concluded that gender, employment status, health insurance participation, family support, and treatment motivation have significant correlations with patient adherence behavior in the context of CHD at the Bandung Heart Clinic.